Akkermansia muciniphila ameliorates depressive disorders in a murine alcohol-LPS (mALPS) model. Issue 24 (23rd November 2022) - Guo, Dingming; Park, Chaiwoo; Li, Yun; Li, Bei; Yang, Qianqian; Deng, Yun; Gao, Na L.; Li, Rong; Wang, Xiangfeng; Yi, Liwen; Liu, Zhi
Abstract : Depression is the most common mental disorder in the world. Abstract : Depression is the most common mental disorder in the world. Recently, an increasing number of studies have reported alcohol-related depression. However, there is no simple, efficient, and time-saving alcohol-related depression animal model yet. Based on the fact that people with alcohol addiction often have impaired gastrointestinal (GI) tract health like dysbiosis, which serves as a primary factor to augment lipopolysaccharides (LPS), we first developed a murine alcohol-LPS model (mALPS), with oral gavage of LPS in acute alcohol treated mice, and successfully observed depression-like symptoms. We found that acute alcohol treatment damaged the intestinal barrier and caused dysbiosis, which further increased the translocation of LPS and neuroinflammatory responses (TNF-α and IL-1β) and led to abnormal expression of the depression-related genes, i.e. BDND and IDO, reduced the levels of 5-HT and caused depressive behaviors in mice. Probiotic intervention could improve depressive symptoms without notable adverse effects. Akkermansia muciniphila (AKK), one of the next-generation probiotics, has been widely used for the restoration of the intestinal barrier and reduction of inflammation. Here, we found that AKK significantly ameliorated alcohol-related depressive behaviors in a mALPS model, through enhancing the intestinal barrier and maintaining the homeostasis of the gut microbiota. Furthermore, AKK reduced serum LPS, ameliorated neuroinflammation (TNF-α and IL-1β), normalized the expression of depression-related genes and increased the 5-HT levels in the hippocampus. Our study suggests that AKK supplements will be a promising therapeutic regime for alcohol-associated depression in the future.